Evaluation of sublethal effects of ipomoea cairica linn. extract on life history traits of dengue vectors - Zuharah, W.F.; Ahbirami, R.; Dieng, H.; Thiagaletchumi, M.; Fadzly, N. (Instituto de Medicina Tropical de Sao Paulo, 2016)
Plant derived insecticides have considerable potential for mosquito control because these products are safer than conventional insecticides. This study aimed to investigate sublethal activities of Ipomoea carica or railway creeper crude acethonilic extract against life history trait of dengue vectors, Aedes albopictus and Aedes aegypti. The late third instar larvae of Ae. albopictus and Ae. aegypti were exposed to a sublethal dose at LC50 and larvae that survived were further cultured. Overall, Ipomea cairica crude extracts affected the whole life history of both Aedes species. The study demonstrated significantly lower egg production (fecundity) and eggs hatchability (fertility) in Ae. albopictus. The sublethal dose of crude extracts reduced significantly the width of larval head capsule and the wing length of both sexes in both Aedes species. The significance of sublethal effects of I. cairica against Aedes mosquitoes was an additional hallmark to demonstrate further activity of this plant despite its direct toxicity to the larvae. The reduced reproductive capacity as well as morphological and physiological anomalies are some of the effects that make I. cairica a potential candidate to be used as a new plant-based insecticide to control dengue vectors.